Two eARCHT3.0 Lines for Optogenetic Silencing of Dopaminergic and Serotonergic Neurons - Krol, Alexandra; Lopez-Huerta, Violeta G.; Corey, Taylor E. C.; Deisseroth, Karl; Ting, Jonathan T.; Feng, Guoping (Frontiers in Neural Circuits, 2019)
Dopaminergic and serotonergic neurons modulate and control processes ranging from reward signaling to regulation of motor outputs. Further, dysfunction of these neurons is involved in both degenerative and psychiatric disorders. Elucidating the roles of these neurons has been greatly facilitated by bacterial artificial chromosome (BAC) transgenic mouse lines expressing channelrhodopsin to readily enable cell-type specific activation. However corresponding lines to silence these monoaminergic neurons have been lacking. We have generated two BAC transgenic mouse lines expressing the outward proton pump eArchT3.0 and GFP under control of the regulatory elements of either the dopamine transporter (DAT) (Jax# 031663) or the tryptophan hydroxylase (Tph2) (Jax# 031662) gene locus. We demonstrate highly faithful and specific expression of these lines in dopaminergic and serotonergic neurons respectively. Additionally we validate effective and sensitive eArchT3.0-mediated silencing of these neurons using slice electrophysiology as well as with a well-established behavioral assay. These new transgenic tools will help expedite the study of dopaminergic and serotonergic system function in normal behavior and disease.